A Novel BTK Gene Mutation in a Child With Atypical X-Linked Agammaglobulinemia and Recurrent Hemophagocytosis: A Case Report - Han, Shu-Ping; Lin, Yung-Feng; Weng, Hui-Ying; Tsai, Shih-Feng; Fu, Lin-Shien (Frontiers in Immunology, 2019)
X-linked agammaglobulinemia (XLA), caused by a mutation in the Bruton’s tyrosine kinase (BTK) gene, is rarely reported in patients with recurrent hemophagocytic lymphohistiocytosis (HLH). This mutation leads to significantly reduced numbers of circulatory B cells and serum immunoglobulins in patients. Therefore, they exhibit repetitive bacterial infections since infancy, and immunoglobulin (Ig) replacement therapy is the primary treatment. HLH is a life-threatening condition with manifestations of nonremitting fever, hepatosplenomegaly, cytopenias, coagulopathy, lipid disorder, and multiple organ failure. It is caused by the immune dysregulation between cytotoxic T cells, NK cells, and histiocytes. The treatment is based on HLH-2004 protocol including immunotherapy, chemotherapy, supportive therapy, and the stem cell transplantation. However, as we know more about the classification and pathophysiology of HLH, the treatment is modified. T-cell-directed immune therapy is effective in patients with primary HLH, and strong immunosuppression is contraindicated in patients with severe ongoing infections or some PIDs. Here, we report the case of a 7-year-old boy who presented with ecthyma gangrenosum and several episodes of pyogenic infections during childhood. At the age of 5 years, he exhibited cyclic HLH every 2-3 months. The remission of HLH episodes finally achieved after he received monthly Ig replacement infusions (400 mg/kg) at the 4th HLH. However, transient elevation of IgM was incidentally discovered after 6 cycles of monthly Ig replacement therapy. IgM-secreting multiple myeloma, Waldenström's macroglobulinemia, and lymphoma were excluded. The IgM levels then declined and returned to the normal range within a year. The patient and his parents received whole-genome sequencing analysis. It revealed a novel hemizygous c.1632-1G>A mutation in the BTK gene, and XLA was diagnosed. XLA exhibits a spectrum of clinical and immunological presentations in patients. The identification of the mutation in the BTK gene contribute to an accurate diagnosis. Ig replacement therapy is the primary treatment for HLH in patients with XLA.